Global Strategy for the Conservation and Use of Coconut Genetic Resources 2018 -2028: summary brochure - Johnson, V.; Bourdeix, Roland; Prades, A.; Picq, C. (Bioversity International, 2018)
This summarises the Global Strategy for the Conservation and Use of Coconut Genetic Resources, introducing context & status of coconut germplasm conservation and use. Its 7 objectives are: i) strengthen commitment to conserve & use coconut genetic resources (CGR); ii) ensure sustainable ex situ CGR conservation; iii) assess coconut genetic diversity, identify critical gaps in ex situ collections, & implement collecting missions; iv) strengthen in situ conservation & ensure high quality planting material available/used; v) develop resources for safe international germplasm movement; vi) enhance CGR use by better germplasm characterization and evaluation; vii) re-enforce COGENT as a global platform serving Strategy implementation. Use Adobe Reader to view double page layout of brochure.